Analisis Determinan Terjadinya Fraud Di Pemerintahan - Rokhim, Syaipul; Jaya, I Made Laut Mertha (Gorontalo Accounting Journal, 2021)
The 2018 Corruption Perception Index (CPI) data states that Indonesia is in 89th position out of 180 other countries. The purpose of this study is to determine the factors of fraud in the government sector. This study used a sample of 150 employees of government agencies in Indramayu Regency. Data collection by using a questionnaire. The sampling technique uses convenience sampling. Analysis of the data using Structural Equation Modeling (SEM) with smartPLS. The results of the study found that leadership style, effectiveness of internal control, suitability of compensation, organizational ethical culture and law enforcement had no effect on the existence of fraud in the Indramayu Regency Government. Meanwhile, organizational commitment has been shown to have a positive effect on fraud in the Indramayu Regency Government. This study provides a new argument where hard work is needed to eradicate fraud in the government environment. It takes cooperation, commitment, and self-awareness from all elements of society so that fraud can be suppressed.